Implementation Of Video “Sri Mantab” As An Effort To Increase Efforts To Detect Independent Early Detection In The Group Of Pregnant Women - Yanik Muyassaroh; Anjar Astuti (JURNAL KEBIDANAN, 2023)
One of the factors causing death indirectly is late knowing of the danger signs of pregnancy. To anticipate this, it is necessary to identify complications of pregnancy or danger signs of pregnancy. One effort to improve the handling of cases of complications in pregnancy is to provide health education about the danger signs of pregnancy to pregnant women. There are still many pregnant women and their families who do not understand and have not applied the health information contained in the MCH handbook. So, to respond to this, the provision of health education about the early detection of danger signs in pregnant women can take advantage of technological advances using audiovisual media. the purpose of this research is to analyze whether there is an increase in knowledge, attitudes, and behavior of pregnant women using video. This research is a quasi-experimental study using a pre-posttest design with a control group. Bivariate analysis in this study was carried out on the independent and dependent variables using 2 different treatment groups, then the analysis in this study used the unpaired t-test using the Mann-Whitney test. The results of this study show that there is a difference in the increase in the average score of knowledge, attitudes, and behavior of pregnant women after being given counseling using video. from statistical test results, there were significant differences in the variables of knowledge, attitudes, and behavior between the treatment and control groups with p = 0.000. It is hoped that the provision of health education can use a variety of media, one of which is by utilizing audio-visual media for pregnant women which is useful for increasing knowledge, attitudes, and behavior regarding the early detection of danger signs in pregnancy.